PENGARUH PAHAM KEAGAMAAN TERHADAP ETOS KERJA PEDAGANG PASAR SENTRAL KABUPATEN PINRANG - Muliati, Muliati (P3M STAIN Parepare, 2016)
This study discusses about the influence of religious ideas on the work ethic Pinrang central market traders. The research method used in this study is associative research methods with quantitative data. The data collection method used is the technique of observation, interviews and questionnaires, while data analysis method used is descriptive test and product moment correlation test. The research found : first, the level of religious understanding central market traders classified category Pinrang high/good. Second, the level of work ethic central market traders belonging to the category Pinrang enough/being. Third, there is the influence of the religious understanding of the work ethic Pinrang central market traders, relatively weak effect (0.374) with a coefficient determinant only as much rest as much as 13.99 % 86.01 % determined more by factors/other variables. In the rules of significance testing, statistical data obtained tcount t tabel1 â¤ 3.291, 296/1, 671. Thus, the influence of religious ideas on the work ethic significant Pinrang central market merchants.The implications of this research into the repertoire of the intellectual in the field of theology and social studies as well as a part of the academic attitude to participate in contributing ideas to the nation and society on umumnya. Exept that, expected Pinrang local governments would be able to notice that the current setting so the market stall no los who have closed roads that are not passed by the buyer. This situation makes it one of los middle east and the west to experience a place that is not a strategy. It all makes a lot of loss for the seller.